Poor mental health in patients with symptomatic osteochondral lesions of the talus - Juliëtte H. M. Pijnacker; Nathanael O. Agyeman-Prempeh; Inger N. Sierevelt; Kaj S. Emanuel; Birit Broekman; Gino M. M. J. Kerkhoffs; Sjoerd A. S. Stufkens (The Bone & Joint Journal, 2026)
Aims Osteochondral lesions of the talus (OLT) can cause pain and functional limitations, potentially affecting mental health. This study aimed to compare mental health in patients with OLT to the general Dutch population and individuals with mood or anxiety disorders, and to identify factors associated with mental health in OLT patients. Methods This prospective study included patients with symptomatic OLT prior to treatment. Data for the general population and individuals with mood or anxiety disorders were obtained from the Netherlands Mental Health Survey and Incidence Study-3. Mental health was assessed using the Mental Health Inventory-5 (MHI-5). The primary outcome was the mean difference in MHI-5 between OLT patients and the general population. Multivariate linear regression examined associations between mental health and age, sex, BMI, smoking, lesion characteristics, laterality, and Foot and Ankle Outcome Score (FAOS) pain. Results Among the 358 included OLT patients, 87% (311 of 358) scored ≤ 76 on the MHI-5. OLT patients scored significantly lower than the general population (mean difference 20.2 (95% CI 18.9 to 21.5)) and showed similar scores to individuals with a mood or anxiety disorder (mean difference 2.0 (95% CI -0.3 to 4.3)). One and two years after treatment, 79% (170/214) and 78% (134/173) of patients, respectively, scored ≤ 76 on the MHI-5. Multivariate analysis identified smoking (β = -2.6 (95% CI -4.7 to -0.4)) and FAOS pain (β = 0.3 (95% CI 0.1 to 0.3)) significantly associated with MHI-5 scores. Conclusion Poor mental health is highly prevalent in patients with OLT, with scores substantially lower than the general population and comparable with individuals with mood or anxiety disorders. Smoking and ankle pain were associated with worse mental health. Despite successful long-term clinical outcomes of treatment of OLT, mental health remained poor. These findings underscore the importance of integrating mental health interventions alongside orthopaedic care for patients with OLT. Cite this article: Bone Joint J 2026;108-B(9):1147–1153.